2016
DOI: 10.1007/s40618-016-0461-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and clinical consequences of starting androgen therapy in men with low testosterone: results from the SIAMO-NOI registry

Abstract: Management of LOH in SIAMS centres is in line with the international guidelines and the newest knowledge about the role of T on prostate health. Androgen therapy is associated with an improvement in all the aspects of sexual life and in the perception of physical strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In addition, the agreement of the observations on erectile function, as derived from SIEDY, with objective measures derived from PCDU assessment, further reassures on the reliability of our instruments. As a further source of confidence, SIEDY and ANDROTEST have been used in multicenter studies 38,39 providing consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the agreement of the observations on erectile function, as derived from SIEDY, with objective measures derived from PCDU assessment, further reassures on the reliability of our instruments. As a further source of confidence, SIEDY and ANDROTEST have been used in multicenter studies 38,39 providing consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids can induce several hypogonadism-related signs and symptoms, including sexual dysfunction, mood impairment, fatigue, weight gain and osteoporosis [ 16 – 18 , 86 ], and these are described in more detail in the following sections. Regardless of the origin of hypogonadism, signs and symptoms are dependent on the age at onset [ 87 , 88 ]. In adults and aging men, sexual dysfunction is the most specific symptom associated with low testosterone [ 89 91 ].…”
Section: Methodsmentioning
confidence: 99%
“…96 Similar results were derived from another Italian registry (SIAMO-NOI), which collected data from 432 men with hypogonadism in 15 centers. 98 In addition, data derived from either animal models or clinical observations have documented that HG is characterized by an increased prostate inflammation, particularly evident in patients with obesity and metabolic disorders, which can contribute to benign prostatic hyperplasia-related symptoms and can be improved by TRT, explaining, at least partially, the aforementioned observations. Accordingly, preliminary data from a placebo-controlled RCT, involving 120 men with MetS and benign prostatic hyperplasia, showed that TRT produced a moderate improvement in lower urinary tract symptoms, associated with a significant decline in prostate artery flow velocity and acceleration, as assessed by transrectal color Doppler ultrasound, and with a decrease, in the prostatic tissue, of the expression of some inflammation-related genes, such as cyclooxygenase-2, monocyte chemoattractant protein-1, and related orphan receptor gamma-t. 99 A final point to be discussed is related to the effect of TRT in men treated for PC.…”
Section: Prostatementioning
confidence: 99%